1988
DOI: 10.1111/j.1464-5491.1988.tb01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Group Education for Obese Patients with Type 2 Diabetes: Greater Success at Less Cost

Abstract: It has been suggested that much effort expended in teaching diabetic diets is ineffective and wasteful. We have tested a different system by randomly allocating 75 newly diagnosed obese Type 2 diabetic patients to usual 'unstructured' clinic care or to group education by diabetes specialist nurses and a dietitian. Patients allocated to group education attended five 90-min group sessions during the first 6 months. Six months after diagnosis they had lost more weight (median (95% Cl), 7 (5.5-9) vs 2(1-5)kg, p le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 9 publications
0
90
0
1
Order By: Relevance
“…The amount of weight loss in the intervention group (À2.4 kg) resulted in a significant decrease in hemoglobin Alc (HbAlc) of 2.4%. Heller et al (1988) reported similar results in a randomized study where a weight loss of 5 kg was achieved through diet, resulting in a significant reduction of HbAlc of 2% at 6 months.…”
Section: Introductionmentioning
confidence: 53%
“…The amount of weight loss in the intervention group (À2.4 kg) resulted in a significant decrease in hemoglobin Alc (HbAlc) of 2.4%. Heller et al (1988) reported similar results in a randomized study where a weight loss of 5 kg was achieved through diet, resulting in a significant reduction of HbAlc of 2% at 6 months.…”
Section: Introductionmentioning
confidence: 53%
“…Lifestyle interventions were generally more effective in group settings, with positive outcomes noted for weight loss (8,36,47,48,72,74,76,77,94) and glycemic control (31,36,71,76,79), although two studies of lifestyle interventions in individual settings had positive effects on weight (38,80). Both individual (38,39,66 -68) and group (72,75,93) lifestyle interventions had positive effects on diet and self-care behaviors.…”
Section: Effectiveness Of Interventionsmentioning
confidence: 99%
“…Thirteen studies demonstrated positive effects on weight loss; the average weight loss for these studies was ϳ2 kg (range 1.3-3.1) (28,36,38,47,66,72,74,76,80,82,84,89). Most studies with positive results involved regular contacts or reinforcement sessions (38,47,66,76,82,84) or very short follow-up periods (72,74), although four studies had follow-up periods of Ն5 months (36,38,80,82).…”
Section: Cardiovascular Disease Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,7 Group education is a costeffective alternative to individual education. 6,8,9 Fiscal intermediaries and reimbursement constraints are important factors influencing the format of diabetes education in today's practice. The federal Balanced Budget Act of 1997 resulted in changes in reimbursement by the Centers for Medicaid and Medicare Services (CMS, formerly the Health Care Financing Administration) that supported group delivery of diabetes education.…”
Section: Why Group Education?mentioning
confidence: 99%